Peningkatan Daya Saing UMKM Ambar Wedang Klasik melalui Penguatan Manajemen Usaha, Strategi Pemasaran, dan Inovasi Kemasan Produk - Hastuti Indra Sari; Mulyadi Nursi; Rahmadiana Rahmadiana; Henny Risnawati; Azizah Mentari Banyusufi (UNIVERSITAS BHAMADA SLAWI, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in supporting economic growth and improving community welfare. However, many MSMEs still face challenges in business management, marketing, and product packaging development. These challenges were also experienced by Ambar Wedang Klasik, an MSME located in West Cikarang that produces various traditional herbal beverages, including ginger rice drink (wedang kencur), ginger drink (wedang jahe), lemongrass drink (wedang sereh), honey lemon drink, honey lemon tea drink, and stamina herbal drink. This community service program aimed to enhance the business capacity of the partner through strengthening business management, marketing, and product packaging. The methods employed included observation, training, mentoring, monitoring, and evaluation. The training focused on simple financial bookkeeping, business administration, digital marketing through social media, and the development of more attractive and informative product packaging designs. The results demonstrated improvements in the partner’s knowledge and skills in managing the business, utilizing digital media as a promotional tool, and developing more professional product packaging. The program also produced several outputs, including a simple bookkeeping system, strengthened product branding, and redesigned packaging to support business competitiveness. Therefore, this community service activity successfully addressed the partner’s business challenges and contributed to the sustainable development and competitiveness of the MSME.